Integrated Analysis of the Cecal Microbiome and Plasma Metabolomics to Explore NaoMaiTong and Its Potential Role in Changing the Intestinal Flora and Their Metabolites in Ischemic Stroke - Lin, Huiting; Chen, Shaoru; Shen, Lin; Hu, Tao; Cai, Jiale; Zhan, Sikai; Liang, Jiayin; Huang, Mingmin; Xian, Minghua; Wang, Shumei (Frontiers in Pharmacology, 2022)
Ischemic stroke (IS), as a leading cause of disability worldwide, affects intestinal bacterial communities and their metabolites, while recent discoveries have highlighted the importance of the intestinal microflora in the development of IS. Systematic investigations of complex intestinal bacterial communities and their metabolites during ischemic brain injury contribute to elucidate the promising therapeutic targets for IS. However, the associations between intestinal microbiota and related circulating metabolic processes in IS remained unclear. Hence, to identify the changing microflora and their metabolites in IS of NaoMaiTong (NMT), an effective clinical medication, we established the middle cerebral artery occlusion/reperfusion (MCAO/R) model using conventionalized and pseudo-germ-free (PGF) rats. Subsequently, we systematically screen the microflora and related metabolites changing in IS via an integrated approach of cecal 16S rRNA sequencing combined with plasma metabolomics. We found that NMT relies on intestinal flora to improve stroke outcome in conventionalized rats while the protection of NMT was reduced in PGF rats. Total 35 differential bacterial genera and 26 differential microbial metabolites were regulated by NMT. Furthermore, L-asparagine and indoleacetaldehyde were significantly negatively correlated with Lachnospiraceae_UCG.001 and significantly positively correlated with Lachnoclostridium. Indoleacetaldehyde also presented a negative correlation with Lactobacillus and Bifidobacterium. 2-Hydroxybutyric acid was strongly negatively correlated with Ruminococcus, Lachnospiraceae_UCG.001 and Lachnospiraceae_UCG.006. Creatinine was strongly negatively correlated with Akkermansia. In summary, the research provided insights into the intricate interaction between intestinal microbiota and metabolism of NMT in IS. We identified above differential bacteria and differential endogenous metabolites which could be as prebiotic and probiotic substances that can influence prognosis in stroke and have potential to be used as novel therapeutic targets or exogenous drug supplements.